Right ventricular myocardial oxygen tension is reduced in monocrotaline-induced pulmonary hypertension in the rat and restored by myo-inositol trispyrophosphate - Marta Oknińska (Nature Portfolio, 2021)
Abstract Pulmonary hypertension (PH) initially results in compensatory right ventricular (RV) hypertrophy, but eventually in RV failure. This transition is poorly understood, but may be triggered by hypoxia. Measurements of RV oxygen tension (pO2) in PH are lacking. We hypothesized that RV hypoxia occurs in monocrotaline-induced PH in rats and that myo-inositol trispyrophosphate (ITPP), facilitating oxygen dissociation from hemoglobin, can relieve it. Rats received monocrotaline (PH) or saline (control) and 24 days later echocardiograms, pressure–volume loops were obtained and myocardial pO2 was measured using a fluorescent probe. In PH mean pulmonary artery pressure more than doubled (35 ± 5 vs. 15 ± 2 in control), RV was hypertrophied, though its contractility was augmented. RV and LV pO2 was 32 ± 5 and 15 ± 8 mmHg, respectively, in control rats. In PH RV pO2 was reduced to 18 ± 9 mmHg, while LV pO2 was unchanged. RV pO2 correlated with RV diastolic wall stress (negatively) and LV systolic pressure (positively). Acute ITPP administration did not affect RV or LV pO2 in control animals, but increased RV pO2 to 26 ± 5 mmHg without affecting LV pO2 in PH. RV oxygen balance is impaired in PH and as such can be an important target for PH therapy. ITPP may be one of such potential therapies.